Depression and socioeconomic stressors in expectant parents with fetal congenital anomalies. (12th December 2022) - Kim, Amanda J. H.; Servino, Lauren; Bircher, Sam; Feist, Cori; Rdesinski, Rebecca E.; Dukhovny, Stephanie; Shaffer, Brian L.; Saxton, Sage N.
Abstract: Objective: Congenital anomalies are increasingly diagnosed before birth, which may lead to psychological distress in expectant parents. While the presence of significant symptoms of depression and stress in these parents is established, understanding their context within parents' other life stressors has not been fully investigated. We sought to characterize the socioeconomic profile and depression symptoms of expectant parents in a quaternary care academic hospital's fetal care clinic. Methods: This prospective observational study enrolled pregnant persons and their partners in our fetal care clinic. The Edinburgh Postpartum Depression Scale (EPDS), Tool Assessing Patient Stress (TAPS), and a sociodemographic survey were utilized to assess parent psychological distress and socioeconomic stressors. Results were analyzed by the severity of the fetal anomaly. EPDS was repeated at two weeks postpartum. Results: 21.7% of pregnant subjects and 25.0% of co-parents had a positive screen on the EPDS at enrollment during their pregnancy. Mothers' EPDS scores correlated with the severity of the fetal anomaly. Many parents reported socioeconomic stressors including: living remotely from the medical center, low household income, food insecurity, unemployment, or other employment concerns, and difficulty affording living expenses. Most also reported factors that can mitigate psychological distress including social support and participation in a religion or faith. Conclusions: Expectant parents with fetal anomalies should be screened for depression as well as social and economic risk factors that place them and their infants at higher risk for poor health outcomes. Further work is needed to determine the optimum interventions for addressing their depression symptoms and reducing socioeconomic stressors.